Evaluating implementation outcomes (acceptability, adoption, and feasibility) of two initiatives to improve the medication prior authorization process - Laney K. Jones (BMC, 2021)
Abstract Background Processes such as prior authorization (PA) for medications, implemented by health insurance companies to ensure that safe, appropriate, cost-effective, and evidence-based care is provided to all members, have created inefficiencies within healthcare systems. Thus, healthcare systems have implemented supplemental processes to reduce burden and ensure efficiency, timeliness, and appropriate care. Objective Evaluate implementation outcomes of two initiatives related to PA for medications: a common record that records all PA-related information that was integrated into the health record and an auto-routing of specialty prescriptions to a hospital-owned specialty pharmacy. Methods We conducted semi-structured interviews with medical staff to understand their experience, acceptability, adoption, and feasibility of these initiatives guided by Proctor’s Framework for Implementation Outcomes. Transcripts were analyzed using consensus coding. Results Eleven medical staff participated in semi-structured interviews. The two initiatives were analyzed together because the findings were similar across both for our outcomes of acceptability, adoption, and feasibility. Participants found the implemented initiatives to be acceptable and beneficial but felt there were still challenges with the new workflow. The initiatives were fully adopted by only one clinic site within the healthcare system, but limitations arose when adopting to another site. Individuals felt the initiatives were feasible and improved workflow, communication, and transparency. However, participants described future adaptations that would help improve this process including improved standardization, automation, and transparency. Conclusion The acceptability, adoption, and feasibility of two initiatives to improve the PA process within the one clinical site were well received but issues of generalizability limited the initiatives adoption system wide.